1996
DOI: 10.1093/ije/25.6.1292
|View full text |Cite
|
Sign up to set email alerts
|

Urban Schistosomiasis: Morbidity, Sociodemographic Characteristics and Water Contact Patterns Predictive of Infection

Abstract: Our results emphasize the need for schistosomiasis control measures focusing on water contacts for leisure purposes in this industrialized urban area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 1 publication
2
24
0
1
Order By: Relevance
“…How-ever, only a small proportion of S. mansoni-infected children recalled having had those particular water contacts over the last month-though most of the non-infected children did not recall them at all. It is interesting to note that recent surveys in Egypt 15 , and three Brazilian studies 24,26,28 pursuing a comparable approach reported similar odds ratios and diagnostic performance for comparable water contact patterns. In one additional Brazilian study, children between 2 and 14 years who reported having had water contacts were 55.8 times more likely to be infected with S. mansoni.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…How-ever, only a small proportion of S. mansoni-infected children recalled having had those particular water contacts over the last month-though most of the non-infected children did not recall them at all. It is interesting to note that recent surveys in Egypt 15 , and three Brazilian studies 24,26,28 pursuing a comparable approach reported similar odds ratios and diagnostic performance for comparable water contact patterns. In one additional Brazilian study, children between 2 and 14 years who reported having had water contacts were 55.8 times more likely to be infected with S. mansoni.…”
Section: Discussionmentioning
confidence: 86%
“…Results showed that questionnaires might be an alternative for self-diagnosis of S. mansoni. [23][24][25][26][27][28] However, parasitological validation in most of these surveys was performed with a single or a double Kato-Katz thick smear, which probably led to many infections (especially the light ones) being missed. 29 This might account to some extent for the moderate diagnostic performance.…”
Section: Introductionmentioning
confidence: 99%
“…methods of collecting and analyzing data, and have been performed in various environments and time periods (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Além disso, este delineamento não teria sido possível porque programas de mobilização comunitária em Minas Gerais voltados para a esquistossomose como parte do PCE/ PCDEN não haviam sido desenvolvidos naquela época em outra localidade além de Patis. A segunda opção seria o delineamento seccional, considerando a infecção pelo S. mansoni como variável dependente 14,15 . A principal vantagem seria a possibilidade de determinar fatores sócio demográficos e padrões de contatos com águas associados à infecção.…”
Section: Discussionunclassified